Canadian evidence-based guideline for frontline treatment of chronic lymphocytic leukemia: 2022 update. (February 2023) - Owen, Carolyn; Banerji, Versha; Johnson, Nathalie; Gerrie, Alina; Aw, Andrew; Chen, Christine; Robinson, Sue
Abstract: Chronic lymphocytic leukemia (cll ) is the most common adult leukemia in North America. In 2018, the first unified national guideline in Canada was developed for the front-line treatment of cll that helped guide treatment across the country. As an update in 2022, a group of clinical experts from across Canada came together to provide input and guidance that included new and innovative treatments and approaches that will continue to provide health care professionals with clear guidance on the first-line management of cll . Recommendations were provided in consensus based on available evidence for the first-line treatment of cll . Highlights: Pre-treatment considerations as recommended include IGHV, p53 and Del17p testing. Watch & Wait is recommended for early stage asymptomatic CLL patients. Recommendation for patients with TP53 aberrations include BTKi or Ven+O. Treatment for young/fit patients (no mut del(17p), TP53 ) includes FCR, BTKi, Ven+O. Treatment for older or comorbid patients is complex and includes Ven+O, BTKi, chemo.